The Nano Revolution: IT and Supply Chain Integration in Small Retailers in the Middle East - Ortega-Jimenez, Cesar Humberto; Mohmmad Alhusban, Abdallah Omar (LACCEI, 2023)
This research paper investigates the impact of integrating Information Technology (IT) and Supply Chain Integration (SCI) on the operational performance of nanostores, small retailers with potential for efficiency gains and competitiveness. The study conducts a systematic literature review of 109 papers published between 2015 and 2023, employing VOSviewer for trend analysis. The research reveals varying emphasis over time, with heightened attention between 2019 and 2021, a dip in 2022, and renewed interest in 2023. However, the investigation uncovers a research gap, particularly in the exploration of SCI and IT integration in nanostores. Developing countries, notably the Middle East, are underrepresented, with only six studies from the United Arab Emirates. The study’s objectives encompass understanding the impact of IT and SCI on nanostore performance and introducing a novel methodological approach using VOSviewer. It underscores the need for further research in these domains, especially in developing nations. The implications of the research guide nanostore managers and policymakers in leveraging IT and SCI for operational enhancement. The study also predicts societal shifts in attitudes, service quality, and quality of life. The research reveals trends, geographic gaps, and a novel approach. Practical applications and policies that shape the nanostore landscape and social well-being.